Effects of practice variability on spinal manipulation learning* - Marchand, Andrée-Anne (J Chiropr Educ, 2017)
OBJECTIVE: To evaluate the effects of practice variability on chiropractic students' capacity to deliver spinal manipulations (SMs) of a targeted peak force. METHODS: Forty students participated in an experimental session including either a variable or a constant practice protocol of 45 SMs. SMs were delivered on a computer-connected device that recorded force-time profiles. Ten SMs with a target peak force of 350-N were performed before practice, immediately following practice, and 2 days later. Mixed-design analyses of variance were used to assess the effect of practice type on SM biomechanical parameters and on the constant, the absolute error (AE), and the variable error (VE). RESULTS: The practice period led to significantly more accurate (F(AE)[2,76] = 6.17, p < .01) and consistent (F(VE)[2,76] = 3.90, p = .02) performances at the postintervention assessment regardless of practice type. Among biomechanical parameters, preload force was higher at the retention assessment than at baseline (F[2,76] = 6.53, p < .01), while rate of force application significantly decreased between the baseline and the retention assessment (F[2,76] = 4.10, p = .02). CONCLUSION: This experimental study showed that 1 session of SM practice including feedback leads to an increase in SM peak force accuracy and consistency, whether or not the practice period included variable practice. The current results confirmed that short practice periods with feedback should be included in the chiropractic curriculum.